Compact thermal networks for modeling packages - Codecasa, L.; D'Amore, D.; Maffezzoni, P. (IEEE transactions on components and packaging technologies, 2004)
In this paper, thermal networks for modeling packages are rigorously introduced. A multipoint moment matching method for state space reduction of these discretized thermal networks is formulated. In this manner reduced thermal networks are derived that can be used as boundary condition independent compact thermal models of packages. This algorithm is successfully applied to the detailed analysis of an idealized ball grid array package.